2015
DOI: 10.1007/s13147-015-0356-5
|View full text |Cite
|
Sign up to set email alerts
|

Immobilienmarkteffekte des Emscherumbaus?

Abstract: Zusammenfassung In Deutschland besteht ein erheblicher Mangel an wissenschaftlichen Erkenntnissen über die Immobilienpreiseffekte von Infrastrukturmaßnahmen in regionalen Kontexten. Mit einem Investitionsvolumen von mehr als 4,5 Mrd. Euro über den Zeitraum von 1991 bis 2020 ist die ökologische Aufwertung der Emscher im nördlichen Ruhrgebiet eines der größten Infrastrukturprojekte Europas. Unter Verwendung von geo-referenzierten Immobiliendaten von ImmobilienScout24, die mit weiteren georeferenzierten Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…external shocks like the 2008 financial crisis and Fukushima's influence on property prices in locations in proximity to nuclear power plants around the world) and internal, city-wide developments (e.g. urban development projects) on local housing markets (Bauer et al, 2017(Bauer et al, , 2015.…”
Section: Data On Hedonic Apartment Characteristicsmentioning
confidence: 99%
“…external shocks like the 2008 financial crisis and Fukushima's influence on property prices in locations in proximity to nuclear power plants around the world) and internal, city-wide developments (e.g. urban development projects) on local housing markets (Bauer et al, 2017(Bauer et al, , 2015.…”
Section: Data On Hedonic Apartment Characteristicsmentioning
confidence: 99%
“…The data also allow to evaluate place-based policy such as the Emscher-Umbau, a large ecological reconstruction measure, analyzed in Bauer et al (2015). Regarding the precise geo-location, the value of specific stationary amenities or disamenities can be evaluated.…”
Section: Existing Evidence and Potential Of The Datamentioning
confidence: 99%
“…First, due to the high market share of ImmobilienScout24, the dataset consists of a substantial number of observations. This allows for analyzing small-scale housing markets, such as the investigation of the effect of policy intervention on local house prices (e. g. Bauer et al, 2015) and house price responses to location-specific shocks (e. g. Bauer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Using six districts of Rhineland-Palatinate as a case study, they found confirming evidence for this question, but differences between those prices do not vary systematically among property types. A uniform or stochastic yet uncorrelated mark-up on transaction prices, however, will not affect estimation results in any case when estimating a hedonic pricing model (Bauer et al, 2015).…”
Section: Building Data From Immobilienscout 24mentioning
confidence: 99%